Method for isolation of soil DNA and PCR based detection of ginger wilt pathogen, Ralstonia solanacearum - M. ANANDARAJ, A. KUMAR* and (Indian Phytopathology, 2006)
An efficient DNA isolation protocol and PCR based detection of bacterial pathogen in soil are described here. The use of this DNA isolation protocol and PCR based method using universal Ralstonia solanacearum specific primer offer a rapid method for unambiguous detection of this pathogen in soil which can be employed for monitoring soil. The PCR based assay could detect the pathogen at a concentration of 103 -104 cells per gram of soil.